Post-Spinal Backache! A Myth or an Overlooked Complication - Hussain, Aftab; Saleem, Muhammad Asif; Feroze, Rehana; Wahid, Faisal; Bajwa, Saleem Pervaiz; Akram, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out the difference in the backache when a 27G Quincke needle with no more than two attempts is used for spinal anaesthesia versus general anaesthesia. Study Design: Prospective comparative study. Place and Duration of Study: Anesthesia Department, Combined Military Hospital, Lahore Pakistan, from Jun 2020 to May 2021. Methodology: A total of 150 patients were divided into two Groups. C-sections were performed under general and spinal anaesthesia in Group-GA and Group-SA, respectively. General anaesthesia was induced with intravenous anaesthetics following rapid sequence induction. The 27G Quincke needle was used for spinal anaesthesia with no more than two attempts. Post-operative follow-ups for backache were carried out at 24-hours, 1, 4 and 12 weeks. Results: At 24-hours post-operative follow-up, 8 patients from the GA-Group and 17 from the SA-Group had backache; the difference was significant (p-value of 0.049). At week-1, two patients from the GA-Group and five from the SA-Group complained of backache (p-value 0.246). Similarly, at week-4, only one patient from the GA Group and four from the SAGroup had backache (p-value 0.127). At the 12-week follow-up, only one patient complained of backache, and she belonged to the SA- Group (p-value 0.316). Conclusion: Spinal anesthesia results in a significantly high frequency of backache as compared to general anaesthesia in the immediate post-operative period; however, there is no long-term difference in backache.